Security Protocols 15th International Workshop, Brno, Czech Republic, April 18-20, 2007. Revised Selected Papers - Christianson, Bruce; Crispo, Bruno; Malcolm, James A.; Roe, Michael; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the thoroughly refereed post-proceedings of the 15th International Workshop on Security Protocols, held in Brno, Czech Republic, in April 2007. The 15 revised full papers presented together with edited transcriptions of some of the discussions following the presentations have passed through multiple rounds of reviewing, revision, and selection. The topics addressed reflect the question "When is a Protocol Broken?" and how can it degrade gracefully in the face of partially broken assumptions, or how can it work under un(der)specified assumptions.
Keywords: Computer science; Computer Communication Networks; Data encryption (Computer science).; Computer software; Information systems; Information Systems; Computer Science; Computer Communication Networks; Data Encryption; Management of Computing and Information Systems; Algorithm Analysis and Problem Complexity; Information Systems Applications (incl.Internet).; Computers and Society